Karakteristik Cuka Makan dari Cairan Pulpa Hasil Samping Fermentasi Biji Kakao pada Penambahan Gula dan Garam - Wartini, NiMade; Wrasiati, Luh Putu; Ganda-Putra, Gusti Putu (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 2 No 2 (2015), 2015)
The purpose of this research were (1) to study the effect time of fermentation naturally inaerobic conditions on content of acetic acid of watery sweating (2) to examine the effect ofadding sugar and salt to the characteristics of the cacao vinegar produced from distillate aceticacid, and (3) to obtain conditions of the process of making cacao vinegar from distilled liquidfrom watery sweating of cocoa beans.Fermentation treatment consists of 6 levels ie 0, 5, 10, 15,20, and 25 days. Fermentation is done naturally in aerobic conditions at room temperature.Aerobic conditions was made with the use of the aerator. Liquid pulp fermented acetic acidlevels observed every 5 days to establish the optimal fermentation. Pulp fermented liquids thatproduce optimal levels of acetic acid distilled vinegar and then made into a cacao vinegar withthe addition of sugar (0.00; 0.05; 0.10 ;, 0.15; and 0.20%) and salt (0, 00; 0.10; 0.15; 0.20; and0.25%).The results showed that the fermentation time for 15 days is optimal fermentation timebecause it can increase the content of acetic acid on the watery sweating (2.65% acetic acid).Best cacao vinegar obtained from treatment of the addition of sugar 0.15% and 0.20% salt. Itscharacteristics as follows : content of acetic acid, pH, total dissolved solids, sugar, and salt were1.24%, 2.71, 3.95%, 0 ,15%, and 0.19%, respectively, hedonic of flavor and aroma were 5.8 and5.3 (rather like to like), respectively.
Keywords: cocoa beans, fermented, watery sweating, acetic acid